Pharmacodynamic characterization of the interaction between abciximab or tirofiban with unfractionated or a low molecular weight heparin in healthy subjects - Klinkhardt, Ute (Blackwell Science Inc, 2001)
AIMS: The objective of our study was to define the interaction between either unfractionated heparin (UFH) or a low molecular weight heparin, reviparin (REV), and the pharmacodynamic profile of the GPIIb/IIIa-antagonists abciximab (ABC) or tirofiban (T). METHODS: Two studies each containing 18 healthy subjects were performed, and all were pretreated with aspirin (ASA) for 3 days. Volunteers then received UFH (5000 IU bolus/infusion 7 IU kg(−1) h(−1) for 7 h, n = 6), REV (4200-anti-Xa-IU s.c., n = 6) or placebo (n = 6). One hour later, ABC (study I) or T (study II) were given by i.v. infusion for 6 h. The pharmacodynamic effects measured were bleeding time (BT), fibrinogen-binding at the GPIIb/IIIa-receptor (FIB), expression of the platelet secretion marker CD62, and ADP (20 µm)- and collagen (5 µg ml(−1))-induced platelet aggregation. RESULTS: After treatment with both GPIIb/IIIa-antagonists, prolongation of BT occurred to a similar magnitude (approximately 25–30 min) and was not affected by UFH or REV-comedication. ABC or T with ASA alone resulted in nearly the same magnitude of reduction in FIB and platelet aggregation. After coadministration with UFH, FIB was significantly higher (thus less inhibited) than after after T + ASA alone (19 ± 16% vs 55 ± 36%) or ABC + ASA alone (8 ± 9% vs 32 ± 11%). This attenuation of FIB was not seen with REV. Inhibition of ADP-and collagen-induced aggregation tended to be attenuated by treatment with UFH (e.g. ADP-induced aggregation at 0.25 h after ABC + ASA alone =13 ± 4%; after coadministration with UFH = 40 ± 26%). No such changes were noted with REV. Minor reductions in CD62-expression were seen in subjects given ABC or T alone, but expression was not affected by UFH or REV. CONCLUSIONS: Co-medication with UFH attenuated platelet inhibition during treatment with GPIIb/IIIa-antagonists, but these effects were not seen with the low molecular weight heparin reviparin. The results show that administration of reviparin together with abciximab or tirofiban did not adversely affect the pharmacodynamic profile of these GPIIb/IIIa-antagonists.